Mycobacterium avium Subspecies paratuberculosis Infection Modifies Gut Microbiota under Different Dietary Conditions in a Rabbit Model - Arrazuria, Rakel; Elguezabal, Natalia; Juste, Ramon A.; Derakhshani, Hooman; Khafipour, Ehsan (Frontiers in Microbiology, 2016)
Mycobacterium avium subspecies paratuberculosis (MAP) the causative agent of paratuberculosis, produces a chronic granulomatous inflammation of the gastrointestinal tract of ruminants. It has been recently suggested that MAP infection may be associated with dysbiosis of intestinal microbiota in ruminants. Since diet is one of the key factors affecting the balance of microbial populations in the digestive tract, we intended to evaluate the effect of MAP infection in a rabbit model fed a regular or high fiber diet during challenge. The composition of microbiota of the cecal content and the sacculus rotundus was studied in 20 New Zealand white female rabbits. The extracted DNA was subjected to paired-end Illumina sequencing of the V3-V4 hypervariable region of the 16S rRNA gene for microbiota analysis. Microbial richness (Chao1) in the cecal content was significantly increased by MAP infection in regular diet rabbits (p = 0.0043) and marginally increased (p = 0.0503) in the high fiber group. Analysis of beta-diversity showed that MAP infection produces deeper changes in the microbiota of sacculus rotundus than in the cecal content. A lower abundance of Proteobacteria in the cecal content of infected animals fed the high fiber diet and also lower abundance of Bacteroidetes in the sacculus rotundus of infected animals fed the regular diet were observed. Based on OPLS-DA analysis, we observed that some bacteria repeatedly appear positively associated with infection in different samples under different diets (families Dehalobacteriaceae, Coriobacteriaceae and Mogibacteriaceae; genus Anaerofustis). The same phenomenon was observed with some of the bacteria negatively associated with MAP infection (genera Anaerostipes and Coprobacillus). However, other groups of bacteria (Enterobacteriaceae family and ML615J-28 order) were positively associated with infection in some circumstances and negatively associated with infection in others. Data demonstrate that MAP infection and diet changes do interact and result in shifts in the microbiota of the cecal content and sacculus rotundus of rabbits.